Activation of the RhoA-YAP-β-catenin signaling axis promotes the expansion of inner ear progenitor cells in 3D culture. (26th March 2020) - Xia, Mingyu; Chen, Yan; He, Yingzi; Li, Huawei; Li, Wenyan
Abstract: Cellular mechanotransduction plays an essential role in the development and differentiation of many cell types, but if and how mechanical cues from the extracellular matrix (ECM) influence the fate determination of inner ear progenitor cells (IEPCs) remains largely unknown. In the current study, we compared the biological behavior of IEPCs in Matrigel-based suspension and encapsulated culture systems, and we found that the mechanical cues from the ECM promote the survival and expansion of IEPCs. Furthermore, we found that the mechanical cues from the ECM induced the accumulation of Ras homolog family member A (RhoA) and caused the polymerization of actin cytoskeleton in IEPCs. These changes in turn resulted in increased Yes-associated protein (YAP) nuclear localization and enhanced expansion of IEPCs, at least partially through upregulating the canonical Wnt signaling pathway. We therefore provide the first demonstration that the RhoA-YAP-β-catenin signaling axis senses and transduces mechanical cues from the ECM and plays crucial roles in promoting the expansion of IEPCs. : Abstract : The study demonstrates that the essential role of RhoA–YAP–β-catenin signaling axis on inner ear progenitor cells expansion. The response of inner ear progenitor cells to mechanical cues from their microenvironment via RhoA-mediated actin cytoskeleton contraction, which lead to nuclear Yes-associated protein (YAP) accumulation. YAP as a mediator of mechanotransduction signaling to promote the expansion of inner ear progenitor cells through regulating β-catenin activity.